Handbook of Japanese lexicon and word formation - Kageyama, Tarō, 1949-; Kishimoto, Hideki (Handbooks of Japanese language and linguistics ;, 2016)
This volume presents a comprehensive survey of the lexicon and word formation processes in contemporary Japanese, with particular emphasis on their typologically characteristic features and their interactions with syntax and semantics. Through contacts with a variety of languages over more than two thousand years of history, Japanese has developed a complex vocabulary system that is composed of four lexical strata: (i) native Japanese, (ii) mimetic, (iii) Sino-Japanese, and (iv) foreign (especially English). This hybrid composition of the lexicon, coupled with the agglutinative character of the language by which morphology is closely associated with syntax, gives rise to theoretically intriguing interactions with word formation processes that are not easily found with inflectional, isolate, or polysynthetic types of languages.